Clinical outcomes in real‐world patients with acute myocardial infarction receiving XIENCE V® everolimus‐eluting stents. Issue 4 (28th March 2013) - Sudhir, Krishnankutty; Hermiller, James B.; Naidu, Srihari S.; Henry, Timothy D.; Mao, Vivian W.; Zhao, Weiying; Ferguson, Joanne M.; Wang, Jin; Jonnavithula, Lalitha; Simonton, Charles A.; Rutledge, David R.; Krucoff, Mitchell W.; et al.
<x xml:space="preserve">Abstract</x> Objectives The objective of this analysis was to evaluate the safety and effectiveness of XIENCE V in acute myocardial infarction (AMI). Background The XIENCE V® Everolimus‐eluting coronary stent was superior to the TAXUS® paclitaxel‐eluting stent in angiographic and clinical outcomes in the SPIRIT II, III, and IV randomized controlled trials, but patients with AMI were excluded. Methods XIENCE V USA is a large, prospective, multicenter, real‐world single‐arm postmarket surveillance trial. Consecutive patients undergoing PCI with XIENCE V were enrolled. For this analysis, clinical outcomes in 673 patients presenting with AMI (STEMI, n = 125) were as compared to patients without AMI (n = 3528) at 1 year. Results At 1 year, ARC‐defined stent thrombosis (ST) rates were 1.08% in AMI vs. 0.85% in the non‐AMI group (P = 0.4987). The late ST (30 days‐1 year) rates were 0.31% vs. 0.47% (AMI vs. non‐AMI, P = 0.7551). Rates of target lesion revascularization (TLR) were 4.1% vs. 4.6% (P = 0.6104), and rates of target lesion failure (TLF) were 9.1% vs. 8.5%, (P = 0.5964). With the historical WHO definition of MI, 1 year TLF rates were 7.0% vs. 6.7% (P = 0.8001). Improvements in quality of life, angina frequency, angina stability, and physical limitations occurred at 6 months (each P < 0.0001) and were sustained at 1 year in both groups. There were no significant differences in clinical outcomes between STEMI and non‐STEMI patients. Conclusions At 1 year, AMI patients treated with XIENCE V had low rates of ST, TLR, and TLF, similar to non‐AMI patients. Marked improvements in patients' health status in this subgroup were also demonstrated. © 2012 Wiley Periodicals, Inc.